Functionalization and characterization of cotton with phase change materials and thyme oil encapsulated in beta-cyclodextrins - Scacchetti, Fabio Alexandre Pereira (2017)
The aim of this work was to study the production of comfortable cotton plain-weave fabrics withantibacterial and antifungal characteristics through a simple finishing process, which consists in apply-ing microcapsules of phase change materials (mPCM), monochlorotriazinyl- -cyclodextrin (MCT- -CD)and thyme oil. The fabrics were characterized by Infrared Spectroscopy (FTIR), Differential ScanningCalorimetry (DSC), Contact Angle and Infrared Thermography. The thyme oil release was also analyzed,as well as the antibacterial and antifungal activity. The materials treated with 20 L/mL of thyme oilhave shown anomalous oil release mechanisms, according to the Korsmeyer-Peppas model, and activityagainst Staphylococcus aureus, Escherichia coli, Trichophyton rubrum, Pseudomonas aeruginosa and Candidaalbicans.Therefore, it was reached the conclusion that mPCM, conjugated with thyme oil encapsulated in MCT- -CD, proved to be an interesting option to produce materials possessing thermoregulation propertieswith putative clinical relevance for the prevention of infections, particularly dermatophytosis.